Chronotopic and Blood Pressure Response to Oral Glucose Load in Chagas’ Disease - Guariento, Maria Elena; Olga, Elza; Muscelli, Ana; Gontijo, José Antonio Rocha (São Paulo Medical Journal, 1994)
Cardiac chronotropic and pressor responses after an oral load of glucose were assessed in sixteen Chagasic subjects and 28 controls by means of blood pressure and pulse rate measurements. Cardiovascular response was correlated with serum insulin and glucose levels. The experiment identified a subgroup of Chagasic subjects (n=8) with a hypoinsulinemic behavior presenting less chronotropic and pressor responses than controls. This may indicate a lower insulin activity and/or an early Autonomic Nervous System dysfunction in this subgroup.